National Preclinical Sepsis Platform: developing a framework for accelerating innovation in Canadian sepsis research - Mendelson, Asher A; Lansdell, Casey; Fox-Robichaud, Alison E; Liaw, Patricia; Arora, Jaskirat; Cailhier, Jean-François; Cepinskas, Gediminas; Charbonney, Emmanuel; dos Santos, Claudia; Dwivedi, Dhruva; Ellis, Christopher G; Fergusson, Dean; et al. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Despite decades of preclinical research, no experimentally derived therapies for sepsis have been successfully adopted into routine clinical practice. Factors that contribute to this crisis of translation include poor representation by preclinical models of the complex human condition of sepsis, bias in preclinical studies, as well as limitations of single-laboratory methodology. To overcome some of these shortcomings, multicentre preclinical studies—defined as a research experiment conducted in two or more research laboratories with a common protocol and analysis—are expected to maximize transparency, improve reproducibility, and enhance generalizability. The ultimate objective is to increase the efficiency and efficacy of bench-to-bedside translation for preclinical sepsis research and improve outcomes for patients with life-threatening infection. To this end, we organized the first meeting of the National Preclinical Sepsis Platform (NPSP). This multicentre preclinical  research collaboration of Canadian sepsis researchers and stakeholders was established to study the pathophysiology of sepsis and accelerate movement of promising therapeutics into early phase clinical trials. Integrated knowledge translation and shared decision-making were emphasized to ensure the goals of the platform align with clinical researchers and patient partners. 29 participants from 10 independent labs attended and discussed four main topics: (1) objectives of the platform; (2) animal models of sepsis; (3) multicentre methodology and (4) outcomes for evaluation. A PIRO model (predisposition, insult, response, organ dysfunction) for experimental design was proposed to strengthen linkages with interdisciplinary researchers and key stakeholders. This platform represents an important resource for maximizing translational impact of preclinical sepsis research.